Fast electronic driver for optical switches - Woolston, Mark R., author; Rocca, Jorge J., advisor; Marconi, Mario C., committee member; Menoni, Carmen S., committee member; Yalin, Azer P., committee member (Colorado State University. Libraries, 2012)
Electronically controlled optical switches are critical components in many optical systems, including pulsed lasers. Solid-state optical switches based upon the Pockels effect are widely utilized in research and industry, however Pockels cells require electronic drivers capable of switching several kilovolts quickly and cleanly. This thesis reviews Pockels cell designs and their typical applications in laser systems, discusses common drive circuit topologies found in literature, and describes the development of a fast, stable electronic driver for half-wave congured Pockels cell optical switches. In a crowded optical environment, it is frequently desirable to locate the Pockels cell at some distance from the driver electronics. The driver was developed to be capable of 1.4 ns optical transition times when connected to a 6 pF Pockels cell via 1.2 meters of 50 ohm coaxial cable. The driver is designed to operate in colliding-pulse mode at 6-8 kV, with 80 ampere typical switch currents. Total switch propagation delay is less than 100 ns, and thermal drift has been measured at less than 50ps/C°. These pulsers are currently used to drive Pockels cells in colliding pulse mode in pulse picking and slicing applications where optical rise times of < 2 ns and low drift are needed. Novel non-invasive diagnostic techniques for measuring and graphing pulse propagation in a repeatable manner along collapsing avalanche transistor chains are presented.
Keywords: avalanche; Pockels; laser; high voltage; electro-optic; pulse